Factors affecting innovative work behavior in Tech-Company: A review findings using artificial intelligence - Saptowinarno, Bambang; Maharani, Anita; Wihadanto, Ake (Privietlab, 2024)
This literature review analyzes the various factors that affect innovative work be- havior (IWB) in tech companies. Given the competitive nature of the tech industry, continuous innovation is vital for maintaining a competitive edge. This review aims to identify the key determinants of IWB in tech companies by examining existing research. Possible factors to be considered include organizational culture, leadership styles, employee characteristics such as creativity and risk-taking, the organizational climate for innovation, and the role of technology. By gaining a deeper understand- ing of these factors, this study aims to contribute insights into fostering innovation in tech companies, ultimately leading to their success and adaptability in a rapidly changing market.